Analisis tataniaga tomat di Kecamatan Sumberejo Kabupaten Tanggamus - Anisah Anisah Ramadona; Sutarni Sutarni; Muhamad Zaini (Journal of Food System & Agribusiness, 2021)
Sumberejo District is one of the highest tomato production centers in Tanggamus Regency. Tomato trading activities are faced with the problem of fluctuating prices and limitations of trading channels at the farmer level, so it is necessary to analyze the tomato trading system if it is seen from the high amount of production in Sumberejo District. The purpose of this research is to identify the trading system activity in the tomato trading system and channel, calculate the margin of the tomato trading system in each trading channel, analyze the efficiency level of the tomato trading channel in each trading channel, analyze the elasticity of price transmission and market structure in the District of Sumberejo. Tanggamus Regency. The method used in this research is qualitative and quantitative methods. The data in this study is to collect primary data and secondary data. The trading activities carried out by farmers include selling tomatoes, assuming risks, and financing. Trading activities in a trading system include selling tomatoes, buying tomatoes, transporting, weighing, taking risks, financing, and market information. There are 3 trading channels formed in Sumberejo District. The trading channel I consists of farmer-traders, gatherers-retailers-consumers. Channel II consists of farmer-wholesaler-retailer. Channel III consists of farmer-trader-gatherer-wholesaler-consumer. The margin values ​​for the trading channel I, the trading channel II, and the trading channel III, each obtained a margin of Rp 3,000, Rp 3,000 and Rp 4,000. Based on several indicators and the value of marketing efficiency, the trading channel II is an efficient channel compared to channels I and III. The value of price transmission elasticity is 0.785 (Et <1). In general, the structure of the tomato market leads to imperfect competition, namely the oligopsony market)